Tailoring π-conjugation and vibrational modes to steer on-surface synthesis of pentalene-bridged ladder polymers - Bruno de la Torre (Nature Portfolio, 2020)
Development of strategies for the synthesis of pi-conjugated polymers is hampered by limited solubility. Here, the authors report a synthetic protocol based on the search for specific vibrational modes through an appropriate tailoring of the p-conjugation of the precursors, in order to increase the attempt frequency of a chemical reaction.